Behaviour of Face Masks Search for Covid-19 Prevention in Indonesia: Trend and Policy Analysis - Risky Kusuma Hartono; Renny Nurhasana (Al-Sihah : The Public Health Science Journal, 2022)
The studies on the Google searching behavior of face masks can be counted as evidence of how far the netizens’ enthusiasm for increasing their knowledge of the proper use of face masks. This current study aimed to analyze the trends in online searching behavior for face masks to prevent Covid-19 in Indonesia. This was conducted quantitatively utilizing Google search trends regarding the comparison between face mask types, including cloth masks, medical masks, and N95 masks in Indonesia after the first case of Covid-19. The mapping of sub-regions with the largest Google Trends filter category was also illustrated in this study. A time-trend analysis was conducted from Google data by describing several policy implementations, including social distancing and transition periods. A correlation analysis was performed by comparing the number of searches for face masks and the total number of Covid-19 cases. It was found that searching for all types of face masks increased in the early stage of the pandemic in Indonesia, while the trend later decreased. After implementing the social distancing policy, the results suggest that searches for cloth masks ranked highest. The increasing number of Covid-19 confirmed cases reduced the tendency of searching behavior for face masks in the category of cloth masks (r2 = -0.1730), medical masks (r2 = -0.1736), and N95 masks (r2 = -0.4329) at p-value <0.05. This study illustrates that the existence of a mandatory policy to use masks will increase mask-seeking behavior in Indonesia.